Development of Jelly Loaded with Nanogel Containing Natural L-Dopa from Mucuna pruriens Seed Extract for Neuroprotection in Parkinson’s Disease - Chuda Chittasupho; Sarin Tadtong; Suwanna Vorarat; Witcha Imaram; Sirivan Athikomkulchai; Weerasak Samee; Vipaporn Sareedenchai; Thanu Thongnopkoon; Siriporn Okonogi; Narisa Kamkaen (Pharmaceutics, 2022)
The first line therapy of patients with Parkinson’s disease, a neurodegenerative disorder caused by the degeneration of dopaminergic neurons, is levodopa (L-dopa) given orally. Recently, the presence of natural L-dopa in the seed of Mucuna pruriens, a tropical legume in the Fabaceae family, was reported and it showed superior efficiency compared with synthetic L-dopa. Therefore, this study aimed to examine the phytochemical compounds, particularly for natural L-dopa, in M. pruriens seed extract and subsequently prepare a nanogel containing the extract prior to incorporation into a jelly formulation for use as a functional food in elderly patients with Parkinson’s disease. The results show that M. pruriens seed extract contains phenolic compounds, flavonoids, tannins, alkaloids, terpenoids, and saponins. The quantitative analysis performed by the HPLC method revealed that spray-dried M. pruriens seed extract contained 5.59 ± 0.21% L-dopa. M. pruriens seed extract possesses a ferric-reducing antioxidant power and shows free-radical scavenging activity, determined by DPPH and ABTS methods, suggesting a distinctive antioxidant ability of the extract. M. pruriens seed extract at 10 ng/mL did not show cytotoxicity against a neuronal cell line (SH-SY5Y cells), kidney cells (HEK293 cells), or Caco-2 cells. Nanogel of M. pruriens seed extract prepared by ionic gelation had the hydrodynamic diameter, polydispersity index and zeta potential value of 384.53 ± 11.24 nm, 0.38 ± 0.05, and −11.23 ± 1.15 mV, respectively. The transepithelial transport of L-dopa in M. pruriens seed-extract nanogel through Caco-2 cells was measured. Nanogel containing M. pruriens seed extract at the concentration of 10 ng/mL exhibited neuroprotective activity. A jelly formulation containing M. pruriens seed-extract nanogel was successfully developed. The prepared jelly exhibited the acceptable physical and microbiological stabilities upon 6 months of the stability test. The half-life of natural L-dopa in jelly were 3.2, 0.9, and 0.6 years for storage conditions at 4, 30, and 40 °C, respectively, indicating the thermal degradation of natural L-dopa. The prepared jelly containing natural L-dopa from M. pruriens seed extract with the prominent antioxidant activity is a promising option for elderly patients suffering from Parkinson’s disease.